Management of Quality Improvement of Graduates of Professional Teacher Education - Fauyan, Muchamad; Majid, Abdul; Rif’iyati, Dian; Abdul Majid (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The Teacher Professional Education (PPG) Program faces challenges in improving the quality of graduates to ensure their relevance to the world of education. This situation results in PPG graduates not being fully prepared to face various dynamics in the school environment. Based on this, the purpose of this study is to analyze the effectiveness of benchmarking and tracer studies in improving the quality of PPG graduates. This study used a mixed approach (qualitative and quantitative) with PPG administrators and alumni from 2021-2022 as subjects. Data collection methods used observation, questionnaires, interviews, and documentation studies. The data collection instrument used a questionnaire sheet. Data analysis techniques used thematic and descriptive analysis. The in-service PPG program showed a positive impact with an average score of 4.28 and a score of 85.54, categorized as "Strongly Agree." The highest aspect was improving teacher professionalism, with a score of 4.39 and a score of 87.96. The 100% pass rate in the 2024 UKMPPG is a key indicator of the program's success. It was concluded that PPG successfully improved pedagogical competence, technological skills, and teacher professionalism. Overall, based on the data obtained, the implementation of benchmarking and tracer studies has successfully improved the quality of PPG graduates. Alumni surveys indicate high satisfaction with the learning materials, the development of learning tools, and instructor performance. Recommendations include strengthening infrastructure and adaptive learning methods. This research contributes to the development of teacher education quality management based on best practices and alumni feedback.